Temperature‐dependent EXAFS study of the local structure and lattice dynamics in cubic Y2O3. (19th February 2016) - Jonane, Inga; Lazdins, Karlis; Timoshenko, Janis; Kuzmin, Alexei; Purans, Juris; Vladimirov, Pavel; Gräning, Tim; Hoffmann, Jan
Abstract : The evolution of the local atomic structure of cubic yttria is followed upon temperature increase using Y K ‐edge X‐ray absorption fine structure analysis, complemented with advanced modelling approaches (classical molecular dynamics, reverse Monte Carlo and evolutionary algorithm methods). Abstract : The local structure and lattice dynamics in cubic Y2 O3 were studied at the Y K ‐edge by X‐ray absorption spectroscopy in the temperature range from 300 to 1273 K. The temperature dependence of the extended X‐ray absorption fine structure was successfully interpreted using classical molecular dynamics and a novel reverse Monte Carlo method, coupled with the evolutionary algorithm. The obtained results allowed the temperature dependence of the yttria atomic structure to be followed up to ∼6 Å and to validate two force‐field models.